Students’ Usage of GenAI in Universities of Applied Sciences: Experiences and Development Needs for Guidance and Support - Silvennoinen, Minna; Aksovaara, Satu; Alanko-Turunen, Merja (38th Bled eConference: Empowering Transformation: Shaping Digital Futures for All: Conference Proceedings, 2025)
This article explores University of Applied Sciences students’ awareness and use of GenAI, as well as their experiences with institutional guidelines and educator support. At the time of data collection, these institutions were in the early stages of GenAI adoption. A survey of 160 students revealed varied uses of GenAI and suggested that a notable proportion of students perceived the guidelines, and their delivery as unclear or inconsistent. Our results indicate that GenAI usage is not yet fully addressed in course-level practices, which may contribute to fragmented and inconsistent use of the technology among students. Moreover, students were more likely to seek help from peers than from educators when encountering difficulties with AI applications, which may reflect students’ perceptions of the limited availability of educator support. The findings support previous research that there is a need for increased awareness of GenAI use in higher education among both students and educators. The study highlights the need for strengthening the role of educators in encouraging and influencing how their students perceive and adopt GenAI technology.